The role of self-esteem on nomophobia with extraversion personality as a moderating variable - Defi Astriani (Jurnal Ilmiah Psikologi Terapan, 2023)
Nomophobia is an individual’s propensity to use smartphones excessively, resulting in feelings of anxiety and panic when away from their devices. Individuals with high self-esteem are typically affable and optimistic, and vice versa. Smartphones are used to escape their disdain for themselves or as a platform for expressing emotions directly or via social media. People who use smartphones excessively in every aspect of their lives will develop a physical dependence on them and become anxious and concerned when they cannot access them. This study examines the relationship between self-esteem and nomophobia using extraversion as a moderating variable. A total of 105 individuals between 18 and 24 were selected using the quota sampling method to participate in this study. The regression test results demonstrate the role of the two predictor variables in extraversion. Moreover, based on the PROCESS model 4 developed by Hayes, it was discovered that the extraversion personality variable had a minor potential to moderate the relationship between self-esteem and nomophobia, thereby providing a buffering effect despite this potential. The frequency of moderation is 0.102, or 10.20%. This indicates that extraversion moderates the impact of self-esteem on nomophobia by 10.20%